Palladium‐Catalyzed Oxidative Cascade Carbonylative Spirolactonization of Enallenols. (16th February 2017) - Qiu, Youai; Yang, Bin; Jiang, Tuo; Zhu, Can; Bäckvall, Jan‐E.
Abstract: A highly selective palladium‐catalyzed oxidative carbonylation/carbocyclization/alkoxycarbonylation of enallenols to afford spirolactones bearing an all‐carbon quaternary center was developed. This transformation involves the overall formation of three C−C bonds and one C−O bond through a cascade insertion of carbon monoxide (CO), an olefin, and CO. Preliminary experiments on chiral anion‐induced enantioselective carbonylation/carbocyclization of enallenols afforded spirolactones with moderate enantioselectivity.